Enhanced bioavailability and hepatoprotectivity of optimized ursolic acid–phospholipid complex. (3rd June 2019) - Biswas, Sayan; Mukherjee, Pulok K.; Harwansh, Ranjit K.; Bannerjee, Subhadip; Bhattacharjee, Pritorthi
Abstract: Objective: To prepare and characterize an optimized phospholipid complex of Ursolic acid (UA) to overcome the poor pharmacokinetic properties and to investigate the impact of the complex on hepatoprotective activity and bioavailability in animal model. Significance: UA is a potential phytoconstituent obtained from several plant sources, which has been explored for its diverse pharmacological activities including hepatoprotection. Its major limitation is poor absorption, rapid elimination, and hence low bioavailability after administration. Methods: Response surface methodology was adopted to formulate an optimized (UA) complex. The complex was characterized by differential thermal analysis (DTA), Fourier transform-Infrared Spectroscopy, Powder X ray Diffraction, molecular docking, etc. The physico-chemical profile (solubility, oil/water partition coefficient) and in vitro dissolution profile was estimated. The formulation was then used to study hepatoprotective activity and bioavailability in animal models. Results: Results showed that the phospholipid complex of UA has enhanced the hepatoprotective potential as compared to pure UA at the same dose level. The complex restored the levels of serum hepatic marker enzymes with respect to untreated group and increased the relative bioavailability of UA in rat plasma by 8.49-fold in comparison with pure compound at the same dose level. It enhanced the elimination half-life ( t 1/2 el ) from 0.69 ± 1.76 to 8.28 ± 1.98 h. Conclusion: Complexation of UA with phospholipid markedly enhanced the hepatoprotective potential of UA by improving its bioavailability and pharmacokinetic parameters. Novelty statement The present article deals with rational optimization of the formulation parameters for phospholipid complex of ursolic acid by Response Surface Methodology analysis, characterizing the formulation by in silico approach apart from conventional instrumental techniques, and evaluating the in vitro dissolution, pharmacokinetics, and hepatoprotective activity of the complex in animals. Novelty statement The present article deals with rational optimization of the formulation parameters for phospholipid complex of ursolic acid by Response Surface Methodology analysis, characterizing the formulation by in silico approach apart from conventional instrumental techniques, and evaluating the in vitro dissolution, pharmacokinetics, and hepatoprotective activity of the complex in animals.